Scientific Prediction of the Covid-19 Pandemic and What Should Society Do? - Iche Andriyani Liberty; Mariatul Fadilah; Hari Kusnanto Josef (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2020)
What is the scientific prediction for the Covid-19 pandemic? Currently, as of April 8, the world’s confirmed cases have over 1.2 million, the death of more than 72 thousand. For Indonesia,  today  2,738  confirmed cases,  221  deaths,  and those who recovered 204.1-3. The update on April 8 today, WHO itself estimates that the Covid-19 Contagion Rate is 1.4 to 2.5. This will form the basis of predictive modeling. Several studies conducted show that currently the basic reproduction number or  R0  of  Covid-19  is higher than SARS.  Initially in the range of  2-3  or an average of  2.5, currently R0 is 1.4 - 6.9. This is what will form the basis of modeling. R0 or the basic reproduction number shows how many people a person can become infected with.  If the R0 is more than 1, we are in an epidemic status as it is today, R0 = 1 endemic, and our R0 is less than 1 we have eradicated. R0 itself consists of three components, namely p: transmission, c: number of contact, and D which is the duration of the infection itself. These calculations are the main points in modeling.